Effect of poly‐γ‐glutamic acid on hydration and structure of wheat gluten. Issue 10 (28th August 2020) - Xie, Xinhua; Wu, Xiuyuan; Shen, Yue; Song, Miao; Xu, Chao; Zhang, Bei; Aziz, Usman; Xu, Xinjun
Abstract : Abstract: In recent years, hydrocolloids have been used extensively as enhancers in dough products. However, studies on the effect of hydrophilic polymers on wheat gluten (WG) within the dough are scarce. In the present study, poly‐γ‐glutamic acid (γ‐PGA), a new and healthy food additive, was added to the WG to investigate its effect on hydration, rheological properties, and structures of WG. Results showed that with the addition of γ‐PGA, the water‐holding capacity (WHC) of WG and the content of bound water increased, whereas the content of immobilized water decreased. In addition, γ‐PGA changed the rheological properties of WG. The elastic properties of WG gradually weakened and the viscous properties gradually increased. Furthermore, scanning electron microscopy (SEM) results showed that with the addition of γ‐PGA, the structure of the WG network became more uniform and the pore size was smaller. A change also occurred in the secondary structure of WG, in which the α‐helix content was significantly reduced while the contents of β‐turn angles were significantly increased, thereby suggesting that γ‐PGA not only functions as a filler in the WG system, but also interacts with WG. From the present study, we conclude that γ‐PGA can interact with WG and water to change the WG secondary structure. γ‐PGA can also restrict moisture migration and enhance the WHC of WG, thereby changing the WG microstructure and improving its functional properties. This condition provides the basis for γ‐PGA to be recommended as WG enhancer for addition in WG‐containing products such as bread, seitan (meat replacement), and others. Practical Application: WG performance plays a key role in the quality of flour products. Thus, many studies have been conducted to improve the WG quality to produce highly popular flour products. The results of this study showed that γ‐PGA can interact with WG and water, and had a good effect on improving the WHC of WG, which means that γ‐PGA has potential usefulness in improving the quality of WG and WG‐containing products such as bread, seitan (meat replacement), and others.